Assessing PET-CT versus conventional CT: a meta-analysis on diagnostic efficacy, prognosis, and post-surgical wound healing in lung mucosal marginal zone lymphoma - Lin, Yang; An, Licai (Frontiers in Oncology, 2026)
ObjectiveThis meta-analysis aims to compare the efficacy of positron emission tomography-computed tomography (PET-CT) and conventional CT in assessing the clinical pathological features, prognosis, and post-surgical wound healing in Lung Mucosal Marginal Zone Lymphoma (LMMZL).MethodsFollowing PRISMA guidelines, a comprehensive search was conducted across databases including PubMed, Scopus, Web of Science, and the Cochrane Library, culminating in the inclusion of 7 studies representing 353 LMMZL patients. Mean difference (MD) or standardized mean difference (SMD) for continuous data, and risk ratio (RR) or odds ratio (OR) for dichotomous data, were used for the meta-analysis, all with 95% confidence intervals (CIs).ResultsPET-CT demonstrated a superior lesion detection rate (LDR) with an SMD of 7.10 (95% CI: 3.17 to 11.02, P < 0.01) and cancer staging detection rate (CSDR) with an SMD of 12.35 (95% CI: 8.99 to 15.7, P < 0.01), compared to conventional CT. A significant reduction in false positive rate (FPR) was noted for PET-CT, indicated by an SMD of -44.74 (95% CI: -66.36 to -23.11, P < 0.01). Additionally, PET-CT was associated with a notable improvement in wound healing outcomes post-surgery, as evidenced by an SMD of -5.93 (95% CI: -8.69 to -3.17, P < 0.01).ConclusionPET-CT emerges as a potentially superior diagnostic tool over conventional CT in evaluating the clinical features, prognosis, and post-surgical wound healing in LMMZL. These findings indicated the advanced imaging techniques on enhancing surgical precision and patient recovery in future diagnostic and therapeutic strategies for LMMZL.